Has your flip flopped? Discovery learning with extraordinary seminars (Journal of Applied Learning and Teaching, 2019)
This instructional paper addresses the often encountered, but rarely published challenge of flipped classroom flops or failures, explaining key wrap-around interventions that were implemented to address observed flip shortcomings using a case-based methodology. Discovery learning with extraordinary seminars was conceived as a lean forwards or active pedagogy for an undergraduate digital marketing module. It comprised three distinct elements: firstly, never-the-same interactive seminars; secondly, conversational plenaries with industry practitioners; and finally, an emboldened ‘fly from the eagle’s nest and soar’ approach to assessment. This learning engagement innovation aims to inspire higher education professionals to overcome their time and risk innovation hurdles. It concludes by sharing a summary of qualitative student feedback and instructor reflections.